2009
DOI: 10.1089/ees.2009.0178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ferrous Ion Coagulation on Biological Ammonium Nitrogen Removal in Treating Coke Wastewater

Abstract: Effects of ferrous ion coagulation in treating coke wastewater were examined through tests. In addition, nitrification tests using coagulated coke wastewater were carried out to evaluate the effect of ferrous ion coagulation on biological ammonium nitrogen removal. Experimental results showed that ferrous ion coagulation was very effective in terms of free cyanide (CN À ) removal. The best free CN À removal was found to be 98% at a ferrous ion dosage of 242 mg Fe 2þ L À1 . In addition, ferrous ion coagulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several of the above-mentioned organic and inorganic compounds present in raw wastewater are toxic even to versatile microorganisms; therefore, prior to biological treatments physical and chemical processes are applied to reduce the concentration of such components. There is a huge variety of methods available for the physical removal (e.g., phenol extraction, ammonia stripping, tar separation, flotation, coagulation) or conversion of contaminants (e.g., conversion of cyanide to thiocyanate with reduced sulfur species, oxidation of heterocyclic compounds) (Chen et al 2019;Kozak and Wlodarczyk-Makula 2018;Maiti et al 2019;Ryu et al 2009), but the detailed discussion of these processes is beyond the scope of this review and could be found elsewhere (e.g., Zhu et al 2018). In addition to the above-mentioned physicochemical treatments, in some cases dilution (e.g., with municipal wastewater or by partial recirculation of purified effluent) is also used to reduce the concentration of toxic contaminants (Maiti et al 2019;Maranón et al 2008;Tong et al 2018).…”
Section: Physicochemical Treatments For the Reduction In Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the above-mentioned organic and inorganic compounds present in raw wastewater are toxic even to versatile microorganisms; therefore, prior to biological treatments physical and chemical processes are applied to reduce the concentration of such components. There is a huge variety of methods available for the physical removal (e.g., phenol extraction, ammonia stripping, tar separation, flotation, coagulation) or conversion of contaminants (e.g., conversion of cyanide to thiocyanate with reduced sulfur species, oxidation of heterocyclic compounds) (Chen et al 2019;Kozak and Wlodarczyk-Makula 2018;Maiti et al 2019;Ryu et al 2009), but the detailed discussion of these processes is beyond the scope of this review and could be found elsewhere (e.g., Zhu et al 2018). In addition to the above-mentioned physicochemical treatments, in some cases dilution (e.g., with municipal wastewater or by partial recirculation of purified effluent) is also used to reduce the concentration of toxic contaminants (Maiti et al 2019;Maranón et al 2008;Tong et al 2018).…”
Section: Physicochemical Treatments For the Reduction In Toxicitymentioning
confidence: 99%
“…Optimal operation parameters for both nitrifying groups (temperature, 20-35 °C ;dissolved oxygen concentration, 3-6 mg/L;and pH, 6.5-8.5;Geets et al 2006;Kim et al 2007;Raper et al 2018a) are necessary for satisfactory bioreactor performance (see also "Appendix"). The nitrification process could be inhibited by several compounds present in the coke effluent (Zhao and Liu 2016), such as phenol and thiocyanate at concentration higher than 100-200 mg/L (Kim et al 2008b), and cyanide higher than 0.1-0.2 mg/L (Kim et al 2007(Kim et al , 2008bRyu et al 2009). Furthermore, nitrite-oxidizing bacteria are more sensitive to low and fluctuating dissolved oxygen concentration than ammoniaoxidizing bacteria (Philips et al 2002).…”
Section: Bacteria Responsible For Nitrogen Removal: Nitrifying and Denitrifying Bacteriamentioning
confidence: 99%
“…It has been proven that nitrogen removal by coagulation only was somewhat ineffective, for the adsorption and meshing of nitrogen by coagulants was limited, which was always lower than 30 and 15% respectively. [17,18] Regarding the removal performance and characteristics of coagulants, the optimal coagulant for our study was PAFC, which was used for further experiments.…”
Section: Coagulant Selectionmentioning
confidence: 99%
“…The metalÀoxo polymer nanobeads were fully characterized in terms of synthetic parameters, composition, structure, and magnetic properties. appropriate size regime are polydispersed in size, 12 and the oxidation of ferromagnetic Fe 3 O 4 to α-Fe 2 O 3 (an antiferromagnet) is quite difficult to prevent. 13 Both problems can compromise the magnetic properties.…”
Section: ' Introductionmentioning
confidence: 99%